2018
DOI: 10.1186/s40170-018-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characterization of isocitrate dehydrogenase (IDH) mutant and IDH wildtype gliomaspheres uncovers cell type-specific vulnerabilities

Abstract: BackgroundThere is considerable interest in defining the metabolic abnormalities of IDH mutant tumors to exploit for therapy. While most studies have attempted to discern function by using cell lines transduced with exogenous IDH mutant enzyme, in this study, we perform unbiased metabolomics to discover metabolic differences between a cohort of patient-derived IDH1 mutant and IDH wildtype gliomaspheres.MethodsUsing both our own microarray and the TCGA datasets, we performed KEGG analysis to define pathways dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 49 publications
11
74
0
Order By: Relevance
“…Recent studies, including one from our own group 12 , have demonstrated that GBMs harboring an isocitrate dehydrogenase 1 (IDH1) mutation represent a metabolically distinct subset of glioma. Because of this, we sought to identify potential differences in FAO utilization between our IDH1 mutant and IDH WT gliomasphere cultures.…”
Section: Fatty Acid Oxidation In Idh1 Mutant Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, including one from our own group 12 , have demonstrated that GBMs harboring an isocitrate dehydrogenase 1 (IDH1) mutation represent a metabolically distinct subset of glioma. Because of this, we sought to identify potential differences in FAO utilization between our IDH1 mutant and IDH WT gliomasphere cultures.…”
Section: Fatty Acid Oxidation In Idh1 Mutant Gbmmentioning
confidence: 99%
“…Wildtype metabolic function of these enzymes is primarily restricted to the TCA cycle where they produce alpha-ketoglutarate through the oxidative decarboxylation of isocitrate.However, these enzymes often incur neomorphic gain-of-function mutations that result in the production of 2-hydroxyglutarate (2-HG) 11 , a proposed oncometabolite, along with widespread changes that extend far beyond the TCA cycle. The effects of IDH mutations have been attributed to altered glucose and nucleotide metabolism, DNA repair capacity, and reactive oxygen species (ROS) regulation, to name a few 12,13,14 . Thus, the mutations present in any given tumor (such as EGFR, PTEN, and IDH1) may determine the extent to which it can adjust to declining substrate availability, pathway inhibition, or therapeutic insult.…”
mentioning
confidence: 99%
“…We chose to inhibit de novo GTP synthesis ( Fig. 3A) because guanylates were the metabolic pathway most correlated with RT-resistance and most GBMs are thought to rely on de novo nucleotide synthesis rather than nucleotide salvage 29 . Drugs inhibiting de novo GTP synthesis, such as mycophenolic acid (MPA) and its orally bioavailable prodrug mycophenolate mofetil (MMF), are FDA-approved to treat immune-mediated disorders and are being investigated as anticancer therapeutics 30 .…”
Section: Inhibition Of De Novo Purine Synthesis Slows Dsb Repair Andmentioning
confidence: 99%
“…Primary GBM (GBM, IDH wild‐type) and IDH ‐wild‐type LGGs usually exhibit a clinically aggressive behavior in comparison with IDH ‐mutant gliomas . Interestingly, it has been reported that IDH ‐mutant and IDH ‐wild‐type tumor cells are distinguishable by metabolic expression profiles . Thus, understanding how IDH ‐wild‐type diffuse gliomas promote metabolic reprogramming may yield crucial insights into glioma pathogenesis and be important from a therapeutic standpoint.…”
Section: Metabolic Reprogramming In Diffuse Gliomasmentioning
confidence: 99%
“…21,22 Interestingly, it has been reported that IDH-mutant and IDH-wild-type tumor cells are distinguishable by metabolic expression profiles. 23 Thus, understanding how IDH-wild-type diffuse gliomas promote metabolic reprogramming may yield crucial insights into glioma pathogenesis and be important from a therapeutic standpoint. Recent studies have revealed that the D-2-HG enantiomer L(S)-2-HG is generated by hypoxia in IDH-wild-type tumors and both 2-HG enantiomers can competitively inhibit α-KG-dependent enzymes.…”
Section: Idh Mutations and Oncometabolites In Gliomasmentioning
confidence: 99%